Diagnostic Accuracy of Transvaginal Versus Transabdominal Ultrasonography for Diagnosing Adnexal Masses - Marriam Rasheed, Shazmeera Urooj, Sana Fatima, Naima Mujahid, Chaudhary Muhammad Arslan Khawar, Muhammad Usman Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Purpose of our study is to diagnose accuracy of transvaginal versus transabdominal ultrasonography for diagnosing adnexal masses. Study Design: Cross-sectional/Comparative study Place and Duration: Sadiq Abassi Hospital Bahawalpur. March 2021 - Oct 21 Methods: There were one hundred and twenty females were presented in this study. Females were aged between 18-55 years. As part of the informed written consent process, all of the patients were asked to provide demographic information including their age, gender, monthly abnormalities (Oligomenorrhea / Amenorrhea), infertility, recurrent pregnancy loss, hirsuitism, and acne vulgaris and obesity. The location, size, borders, echogenicity, soft tissue component, septations, and nodularity of ovarian lesions were evaluated on a grey scale. Patients were equally divided into two groups, group I had 60 cases and received transvaginal ultrasonography while group II received transabdominal ultrasonography with MRI. Outcomes among both groups were compared in terms of frequency of adnexal mass by using histopathological findings (positive/negative). SPSS 25.0 version was used to analyze complete data. Results: There was no any significantly difference between age and body mass index among both groups. Mean parity in group I was 2.34±4.14 and I group II was 1.14±7.38. Infertility and irregular cycle was the most common complaints among both groups in 28 (46.7%), 26 (43.3%) and 21 (35%), 24 (40%). Frequency of adnexal mass in transvaginal ultrasonography was found among 32 (53.3%) but in group II (transabdominal ultrasonography) adnexal mass found in 36 (60%) cases. According to histopathological among 32 cases of transvaginal sonography 26 had true positive and 6 had false negative and in group II 32 cases had true and 4 cases had false positive results. We found that accuracy of transvaginal sonography was lower than that of transabdominal sonography in terms of specificity, positive predictive value and negative predictive value. Conclusion: We concluded in this study that abdominal ultrasonography with MRI was more beneficial and effective in terms of diagnosing adnexal masses with authentic values of specificity and sensitivity.